Ethnicity, Life Satisfaction, Stress, Familiarity, and Stigma Toward Mental Health Treatment. (2nd January 2020) - Crowe, Allison; Kim, Taehee
Abstract : The authors examined the relative contribution of ethnicity, life satisfaction, level of stress, familiarity with mental health treatment, and self‐ and public stigma on attitudes toward mental health treatment among a diverse sample ( N = 632) of adults. Results indicated that ethnicity, stress, familiarity, and self‐stigma of mental illness were significant predictors of attitudes. Additionally, familiarity with mental health treatment moderated the relationship between public stigma and attitude.